L’Événement di Ernaux al cinema: come non tradurre il trauma - Tajani, Ornella (L’ospite ingrato, 2025)
This article proposes a comparison between Annie Ernaux’s L’Événement and the eponymous film adaptation that Audrey Diwan made of it, winning the 78th Venice Film Festival. It will focus on the treatment of the traumatic element, analysing its filmic rendering and placing it in dialogue with Ernaux’s poetics.